Effect of Boiling on Colour, Contents of Betalains and Total Phenolics and on Antioxidant Activity of Colourful Powder Derived from Six Different Beetroot (Beta vulgaris L. var. conditiva) Cultivars - Jan Bárta; Veronika Bártová; Tereza Šindelková; Markéta Jarošová; Zuzana Linhartová; Jan Mráz; Jan Bedrníček; Pavel Smetana; Eva Samková; Ivana Laknerová (Polish Journal of Food and Nutrition Sciences)
Powders prepared from freeze-dried roots of six beetroot ( Beta vulgaris L.) cultivars with red (cv. D'Egypte, Karkulka, Betina, Alexis), yellow (cv. Burpee's Golden) or red-white (cv. Chioggia) colour of root flesh were evaluated before and after boiling treatment (20 min, 100°C). Water and fat holding capacity (WHC and FHC), colour, contents of betalains and total phenolics (TPCs), and antioxidant activity were all significantly affected by cultivar as well as powder thermal treatment. WHC increased after boiling of the powder and varied between cultivars from 2.14 g/g (cv. D'Egypte) to 2.59 g/g (cv. Chioggia). The highest FHC of 1.22 g/g was observed in cv. Betina. Colour stability was optimal in the cultivars with red root flesh; with their lightness decrease between 6 and 10%. This corresponded with betalain content that was the highest in red cv. Betina; for which the values before and after boiling were 18.10 and 15.04 mg/g DM, respectively. Cultivar Betina significantly exceeded the other cultivars also in TPCs and antioxidant activity. The TPCs values of this cultivar were 3.73 and 3.32 mg gallic acid equivalents/g DM in the unboiled and boiled variant, respectively. Antioxidant activity of Betina powder before and after boiling was 11.13 and 11.69 mg ascorbic acid equivalents/g DM, respectively. The results indicated the significance of beetroot cultivar selection for thermal processing. Beetroots with red flesh significantly exceeded yellow and red-white cultivars in all the evaluated characteristics.